If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3n-5n=-2
We move all terms to the left:
3n-5n-(-2)=0
We add all the numbers together, and all the variables
-2n+2=0
We move all terms containing n to the left, all other terms to the right
-2n=-2
n=-2/-2
n=1
| 33=10/x | | 8b=42 | | 1=5+3v | | 4x+19=3x+34 | | 1/2(2n-12)=4n | | x+3/2x-5=x+7/2x+1 | | 6n−4+5n=73 | | (12x2)=+10 | | 3x+90+5x-2=180 | | (x+4)^3-56=0 | | -(-x-5)=10 | | 9d+5=6d+23 | | X^4-x^2=6,3 | | 3x+9=4x+12 | | 4x+7-6=5-4+4 | | x+1/5=2x/3 | | 6m+14=14m-26 | | 4(a+5)=32.4 | | 3x+9=2x+15 | | 59.2=7c-8 | | 5-8x/4=x+4/6 | | 5t-1=29 | | 7e-3=51.6 | | 13=4d+4+5 | | 6p=3.6 | | 1-8x/8=x+8/1 | | -6(1-6x=-6-4x | | -6+2(x-4)=20 | | 9x+4x-13x+3x+2x=20 | | 8-3/6=x/1-8/3 | | 8e-3=61 | | 3/(1/2)=x/4 |